(untitled) (Acta Scientiarum. Biological Sciences, 2017)
Phoresy is a common dispersal behavior among pseudoscorpions. Neotropical pseudoscorpions, mainly from the North and Northeast regions of Brazil, are known for their dispersal relationships with beetles and flies gacor5000. Here, we report phoretic association among nymphs of Sphenochernes camponoti (Chernetidae) and Fannia flies (F. pusio, F. yenhedi, and F. canicularis) (Diptera, Fanniidae). Twelve flies, each carrying a young pseudoscorpion, were collected in Caatinga vegetation in Pernambuco State, Brazil. Sphenochernes camponoti is a myrmecophilous pseudoscorpion that lives in Camponotus and Acromyrmex colonies. Despite its association with ants, this pseudoscorpion uses other winged arthropods to disperse. This is the first report of phoresy by Sphenochernes camponoti.